A 19. század második felében megjelent vallásos ponyvanyomtatványok illusztrációiról - Lengyel Ágnes; Szegedi Vallási Néprajzi Konferencia (6.) (2002) (Szeged) (2006)
Wood engravers of Hungary were mentioned in sources since the beginning of the 16th century. Some 17th and 18th century wood and copper engravings appear even among 19th century illustrations. Nevertheless, the artistic quality of 19th century engravings is poorer than that of the works from the previous centuries. However, for the recipients, it was not the aesthetic value of the pictures, but the represented content and the possibility of everyday use that was important. Devotional pictures played a very important role in the life of peasants, who were not fully literate until the middle of the 20th century. Illustrations of popular religious prints are similar to pictures of prayer books, small icons, and memorial cards of religious associations. Depiction was not necessarily related to content. The illustrations of popular religious prints had their influence on the visual culture of a village. Their influence can also be observed in decorative folk art. The most varied type of illustration in popular religious printsis the iconography of the Virgin Mary. Popular religious prints illustrated by pictures played an important role in children's religious upbringing.
Keywords: Társadalomtudományok; Szociológia; Bölcsészettudományok; Filozófia, etika és vallástudományok; Művészetek (művészetek, művészettörténet, előadóművészetek, zene)